If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3X + -12 + -4X + 12 = X + 3 + -1X + 3 Reorder the terms: -12 + 12 + 3X + -4X = X + 3 + -1X + 3 Combine like terms: -12 + 12 = 0 0 + 3X + -4X = X + 3 + -1X + 3 3X + -4X = X + 3 + -1X + 3 Combine like terms: 3X + -4X = -1X -1X = X + 3 + -1X + 3 Reorder the terms: -1X = 3 + 3 + X + -1X Combine like terms: 3 + 3 = 6 -1X = 6 + X + -1X Combine like terms: X + -1X = 0 -1X = 6 + 0 -1X = 6 Solving -1X = 6 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Divide each side by '-1'. X = -6 Simplifying X = -6
| -8-2x=12 | | 17q^2+19q+2= | | 10x-90=-2x+162 | | 2-8*(-3)+3*(-3)= | | =x^2+6x-3 | | -2a-9=6+15 | | 4x^2-64x=36 | | 2-8*(-3)+3*(-3)=17 | | =5x^2-50x+128 | | -107-2x=40-9x | | 3x^6+12x^4= | | (9/5)b+(3/2)b=-(33/10) | | 3(10+x)=4(x-11) | | 9x^2-24x+16=2 | | 480+3X=5X | | (x-7)(3)=(x)(180-x) | | k/9+19=27 | | 6-2(y-5)=12+3(2y-4) | | 4x+14=78-4 | | 8p=-176 | | X^3+3x^2-100x+96=0 | | x^2-3(x-1)=3x-8 | | 2x^2-x-6= | | 3x+2=2(x+1) | | r+(1/3)-(8/5)=(22/5) | | 3X+480=5X | | 2w*w=18 | | 5x+2=x-10 | | =x^2-10x+11 | | -5(-17a)= | | 4x-4=2x-28 | | (3x+8)+(5x-20)+(5x+4y)= |